Information systems in the process management of commercial SMEs in Canton La Troncal. - Torres Gutama, Juan Luis; Jara Obregón, Luis Stalin (Journal of business and entrepreneurial studie, 2022)
The study will be carried out in Canton La Troncal, the objective is to analyze the importance of information systems in the process management of commercial SMEs. The study was developed under a qualitative approach since it is supported by a bibliographic documentary review. The type of study is descriptive, with a non-experimental design, since the variables were not manipulated in the analysis, only recorded. The results obtained from the study show that information systems in the process management of commercial SMEs allow small and medium-sized companies to advertise their catalog of products and services much more quickly and at a lower cost. It is concluded that technology is key to streamline commercial and productive processes.